First report of salmonella Dublin subdural empyema: A rare presentation of CNS infection - Seif Bugazia; Ahmed Selim; Anuradha Sreenivasan; Mohammed Rehman; Mohammed Mahmoud (IDCases)
Subdural empyema can be precipitated by a range of pathogens. Common clinical symptoms include fever, headache, seizures, and changed mental status. Yet, cerebral infections caused by Salmonella are relatively uncommon as it is rare for Salmonella to invade the central nervous system. We present the first reported case of Salmonella enterica serovar Dublin causing subdural empyema in an 83-year-old female, which was successfully managed with surgical burr hole and drainage in addition to prolonged targeted antimicrobial therapy consisting of 2 g of intravenous Ceftriaxone twice daily for a total of 56 days. This report demonstrates the course of her illness and the corresponding treatment plan; which may help guide medical providers when encountering similar cases.